A Review of Controversial Issues in the Management of Head and Neck Cancer: A Swiss Multidisciplinary and Multi-Institutional Patterns of Care Study—Part 4 (Biomarkers) - Broglie, Martina A.; Dulguerov, Pavel; Henke, Guido; Siano, Marco; Putora, Paul Martin; Simon, Christian; Zwahlen, Daniel; Huber, Gerhard F.; Ballerini, Giorgio; Beffa, Lorenza; Giger, Roland; Rothschild, Sacha; et al. (Frontiers in Oncology, 2019)
Background: The Head and Neck Cancer Working Group of Swiss Group for Clinical Cancer Research (SAKK) has investigated the level of consensus (LOC) and discrepancy in everyday practice of diagnosis and treatment in head and neck cancer. Materials and Methods: An online survey was iteratively generated with 10 Swiss university and teaching hospitals. LOC below 50% was defined as no agreement, while higher LOC were arbitrarily categorized as low (51-74), moderate (75-84%), and high (≥85%). Results: Any LOC was achieved in 62% of topics (n=60). High, moderate and low LOC were found in 18%, 20%, and 23%, respectively. Regarding Head and Neck Surgery, Radiation Oncology, Medical Oncology, and biomarkers, LOC was achieved in 50%, 57%, 83%, and 43%, respectively. Conclusions: Consensus on clinical topics is rather low for surgeons and radiation oncologists. The questions discussed might highlight discrepancies, stimulate standardization of practice, and prioritize topics for future clinical research. Conclusions: Consensus on clinical topics is rather low for surgeons and radiation oncologists. The questions discussed might highlight discrepancies, stimulate standardization of practice, and prioritize topics for future clinical research.